Family History and Risk of Recurrent Cystitis and Pyelonephritis in Women - Scholes, Delia (2010)
PURPOSE: Recurrent urinary tract infections and pyelonephritis have risk factors suggesting genetic sources. Family history variables indicative of genetic risk merit further investigation. We evaluated the risk of recurrent cystitis and pyelonephritis in women with and those without a family history of urinary tract infection. MATERIALS AND METHODS: We conducted a population based case-control study of 1,261 women 18 to 49 years old enrolled in a Northwest health plan. Participants were cases identified from plan databases with documented recurrent cystitis (431) or pyelonephritis (400). Shared controls (430) were similar age women with no urinary tract infection history. We evaluated the history of urinary tract infection and pyelonephritis in first-degree female relatives (mother, sister[s], daughter[s]) and other covariates, ascertained through questionnaires and computerized databases. RESULTS: Of the cases 70.9% with recurrent cystitis and 75.2% with pyelonephritis, and of the controls 42.4% reported a urinary tract infection history in 1 or more female relative (p <0.001 for each case group vs controls). In both case groups odds ratios were significantly increased for women reporting a urinary tract infection history in their mother, sister(s) or daughter(s). Risk increased with a greater number of affected relatives. In women with 1 vs 2 or more relatives the ORs for recurrent cystitis were 3.1 (95% CI 2.1, 4.7) and 5.0 (3.1, 8.1), and the ORs for pyelonephritis were 3.3 (2.2, 5.0) and 5.5 (3.4, 9.0), respectively. CONCLUSIONS: In these community dwelling women a urinary tract infection history in female relatives was strongly and consistently associated with urinary tract infection recurrence and pyelonephritis. Risk estimates increased with stronger family history indices, suggesting a genetic component for increased susceptibility to these infections.